Experimental research with salt crystallization in historic Portuguese azulejos - Esteves, L. (2016)
For five centuries, azulejos have been widely used in Portugal as decorative architectural linings. The most serious form of degradation is the spall of the glaze containing the decoration. Crystallisation of soluble salts is often pointed as its main cause, but that remains yet to be proven. Indeed, there are publications on many simulations of salt decay in porous materials such as stone or brick. However, azulejos have a largely impermeable surface which excludes the possibility of through evaporation, and thus represent a very different physical model. This communication reports a study on the physical degradation of azulejos caused by cycles of dissolution and re-crystallisation of sodium chloride (NaCl). Ageing tests were carried out on 26 Portuguese azulejos from the 17th to the 19th century, some of which with original manufacturing defects or with varying degrees of decay arising from their in situ usage. Ageing cells were developed to try to reproduce conditions to which azulejos are subjected to in walls, namely imbibition from the backside and drying through the glazed surface. The azulejos initially contaminated with a NaCl saturated solution were submitted to 81 accelerated full cycles of imbibition/drying. The tests caused damage in some cases- sometimes very extensive damage indeed- particularly settling in areas where the solution could evaporate freely, but failed to reproduce other sorts of damage often found in situ. It did not verify that the action of NaCl alone could trigger an accelerated loss of glaze in a healthy and properly applied azulejo. Moreover, we concluded that the decaying action of soluble salt is facilitated by pre-existing degradation or defects.